Utilizzo dei ricevitori GNSS a basso costo per l’esecuzione di rilievi topografici di elevata precisione - Donato Tufillaro (GEOmedia, 2024)
The availability of low-cost GNSS receivers opens up new possibilities for performing precision topographic surveys. To achieve acceptable survey precision, it is necessary to use the services provided by a network of permanent stations. The services consist of a stream of differential correction data of the detected positions, transmitted in the RTCM format (Radio Technical Commission for Maritime Services, international standard) which are received through the NTRIP protocol following an authenticated connection to the network site.